Particularidades do pertencimento na pesca artesanal embarcada - Cristiano Wellington Noberto Ramalho; Andreia Patrícia dos Santos (Ciências Sociais Unisinos, 2018)
The present text aims firstly and based on writings of the rural sociology and the socioanthropology of fishing in Brazil at situating the debate about belonging among farmers, and especially artisanal fishermen, and then produce reflections based on field data collected from two fishing communities (Itapissuma and Suape – both in Pernambuco), about the character of the feeling of belonging in embarked artisanal fishing analyzing its singularities and universalities. Therefore, we conducted 36 interviews (18 in each locality mentioned), as well as accompanied the daily life – inland and in the waters – of artisanal fishing professionals. In general, the feeling of belonging assumes, in the studied communities, a common element which identifies them in the condition of social subjects marked with singularities compared to other groups and/or social classes, whether inland (neighborhood relations, relatives’ ties, fishing districts) or in the waters (decisive axis for the symbolic and material way of life of those men).